Antioxidant, Immunomodulatory and Potential Anticancer Capacity of Polysaccharides (Glucans) from Euglena gracilis G.A. Klebs - Casas Arrojo, Virginia; Arrojo-Agudo, María Ángeles; Cárdenas García, Casimiro; Carrillo Fernández, Paloma; Pérez Manríquez, Claudia; Martínez-Manzanares, Eduardo; Abdala-Díaz, Roberto Teófilo (IOAP-MDPI, 2022)
The present study was carried out to determine the bioactivity of polysaccharides extracted from Euglena gracilis (EgPs). These were characterized by FT-IR and GC-MS. Cytotoxicity analyses (MTT) were performed on healthy human gingival fibroblast cell lines (HGF-1), obtaining an IC50 of 228.66 µg mL−1, and cell lines with anticancer activity for colon cancer (HCT-116), breast cancer (MCF-7), human leukemia (U-937, HL-60) and lung cancer (NCl-H460), showing that EgPs have anticancer activity, mainly in HTC-116 cells (IC50 = 26.1 µg mL−1). The immunological assay determined the immunomodulatory capacity of polysaccharides for the production of proinflammatory cytokines IL-6 and TNF-α in murine macrophages (RAW 264.7) and TNF-α in human monocytes (THP-1). It was observed that the EgPs had a stimulating capacity in the synthesis of these interleukins. The antioxidant capacity of polysaccharides and their biomass were analyzed using the ABTS method (18.30 ± 0.14% and (5.40 ± 0.56%, respectively, and the DPPH method for biomass (17.79 ± 0.57%). We quantitatively profiled HGF-1 proteins by liquid chromatography–tandem mass spectrometry analysis, coupled with 2-plex tandem mass tag labelling, in normal cells. In total, 1346 proteins were identified and quantified with high confidence, of which five were considered to be overexpressed. The data is available through ProteomeXchange, under identifier PXD029076.
Keywords: Alimentos funcionales; Euglena gracilis; polysaccharides; Immunomodulatory capacity; Antioxidant activity; Anticancer capacity; Nutraceuticals